Medicaments in periodontal therapy - Witjaksono, Widowati; Rukmo, Mandojo; Mochamad Arief, Erry (Airlangga University Press, 2002)
Medicaments are frequently used before, during and after periodontal therapy. The specific mechanisms of action, side effect,indications and contra indications as well as possible interactions of such medicaments must be understood by the dentist. Before prescribing medicine for dental reasons, the dentist should take the spectrum of activity of the medicaments into consideration. This medicament review will give more information and recommendation that can be made pertaining to the dental medicine in periodontics